Analisis Sistem Informasi Pendistribusian Alat Tulis Kantor di Fakultas Pendidikan Ilmu Pengetahuan Sosial Universitas Pendidikan Indonesia - Dwi Yuliansyah Kusnadi; Gingin Sutisna (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Office equipment, often referred to as Office Stationery (ATK), is a necessity that must be fulfilled and carefully considered in its use in an institution, such as in the Department of Computer Science. Currently, the Department of Computer Science still utilizes Microsoft Excel and handwritten notes in processing ATK data, ranging from the registration of incoming items to the distribution to professors and staff. Therefore, the Department of Computer Science requires a system that can support the process of distributing ATK data. The developed system is expected to assist in generating ATK distribution reports. The system development method chosen in this research is the Waterfall system development model. The system design in this research uses the Unified Modeling Language (UML). The program development process (coding) utilizes the PHP programming language with HTML, and MySQL for database creation. The testing approach in this research employs Black Box testing with the Equivalence Partitioning (EP) method. The results of the conducted testing indicate that all system functions operate according to their intended purposes.